Matters may matter: The disclosure of key audit matters in the Middle East - Osama A. Mah’d (21406955) (2022)
The main objective of this research is to investigate the extent of the disclosure of key audit matters (KAMs) and the factors that affect the level of KAMs’ disclosure in the audit reports of the Middle East (ME) region. A disclosure index approach is employed to consider eight KAMs generated from the International Standard on Auditing (ISA) 701 and a fixed effect regression run on a sample of 281 firms from four countries (Oman, the UAE, Bahrain, and Jordan) for four years (2017–2020), comprising 1124 observations. The findings show that the overall KAMs’ disclosure is approximately 56% across all countries. The study takes into consideration the positive and significant correlation between the leverage, audit committee characteristics, financial industry, audit firm, client size, profitability, liquidity, and KAMs’ disclosure in most sampled countries. This research contributes to our understanding of the level of KAMs’ disclosure and the factors specific to the ME region, which enhances policymakers’ and decision-makers’ knowledge of KAMs’ disclosure in audit reports. Other Information Published in: Cogent Economics & Finance License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23322039.2022.2111787